(untitled) (Encuentros, 2019)
One of the main concerns of teachers has to do with the low academic performance of students. Being able to identify the origin of the difficulty is a real challenge, which is why the executive functions (FE) are analyzed because they are very useful and use for learning. This study included a sample of 30 school students with low academic performance, who were evaluated for FE through the TMT tests, verbal fluency test and Wisconsin card test. The low academic performance was identified through the academic history. It is a study of quantitative approach, descriptive type - transversal and correlational. Most of the participants had a performance below the mean and standard deviation in the Wisconsin letter test in the errors measure, as well as in the phonological FAS and in the TMT part B with some non-significant differences identified by age in other measurements of the tests. There is a statistically significant relationship between self-monitoring and self-correction and FEs: design of plans and programs and efficient resolution of problems in the participants. There is also a relationship between age and the development of the ability to solve problems efficiently, as well as the ability to self-monitor and self-correct. The greater the design of plans and programs, the greater the efficient resolution of problems. There is a need to study other variables that affect the academic performance of school children. The cognitive rehabilitation of the FE, will help in school achievement Keywords: Executive functions; poor academic performance; neuropsychological tests.